The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1365-2281.1998.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intense exercise training on endothelium‐dependent exercise‐induced vasodilatation

Abstract: To determine whether intense exercise training affects exercise-induced vasodilatation, six subjects underwent 4 weeks of handgrip training at 70% of maximal voluntary contraction. Exercise forearm vascular conductance (FVC) responses to an endothelium-dependent vasodilator (acetylcholine, ACH; 15, 30, 60 micrograms min-1) and an endothelium-independent vasodilator (sodium nitroprusside, SNP; 1.6, 3.2, 6.4 micrograms min-1) and FVC after 10 min of forearm ischaemia were determined before and after training. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
2
22
1
8
Order By: Relevance
“…The time-dependent normalization of brachial artery endothelial function raises the possibility that, depending on the time of (re)assessment, previous studies that have not demonstrated an effect of prolonged exercise training on NO-mediated vasodilator function may conceivably have missed the response by measuring it at a limited number of time points. 28,30 The present finding relating to the time course of functional adaptation is also consistent with our recent report of brachial and popliteal changes in function across 8 weeks of lower-limb exercise training. 34 Further research will be required to specifically address the question of whether structural remodeling, which is NO-dependent, 35 may supersede changes in vascular function, is associated with the return of arterial function to resting values.…”
Section: Tinken Et Al Vascular Adaptation To Exercise Trainingdiscussionsupporting
confidence: 93%
“…The time-dependent normalization of brachial artery endothelial function raises the possibility that, depending on the time of (re)assessment, previous studies that have not demonstrated an effect of prolonged exercise training on NO-mediated vasodilator function may conceivably have missed the response by measuring it at a limited number of time points. 28,30 The present finding relating to the time course of functional adaptation is also consistent with our recent report of brachial and popliteal changes in function across 8 weeks of lower-limb exercise training. 34 Further research will be required to specifically address the question of whether structural remodeling, which is NO-dependent, 35 may supersede changes in vascular function, is associated with the return of arterial function to resting values.…”
Section: Tinken Et Al Vascular Adaptation To Exercise Trainingdiscussionsupporting
confidence: 93%
“…However, we did not find a difference in eNOS-dependent reactivity of cerebral arterioles between sedentary and exercised nondiabetic rats. This finding was surprising given the fact that others have shown that ExT increases the reactivity of peripheral blood vessels (5,11,22,37). However, in a previous study (43), we found that ExT did not influence eNOS-dependent responses of the basilar artery.…”
Section: Discussioncontrasting
confidence: 92%
“…However, not all studies are in agreement. Franke et al (22) found that ExT enhanced eNOS-dependent increases in forearm vascular conductance but did not alter vascular responses to eNOS-dependent agonists. In addition, Oltman et al (47) found that ExT did not influence NOS-dependent responses of porcine coronary arteries, and Rogers et al (53) report that ExT actually decreased responsiveness of isolated canine coronary arteries to ␤-adrenergic agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical training appears to en-Serebruany/Davis/Meister/Atar/Whellan/ O'Connor hance endothelial function in healthy young men [157] and in patients with heart failure [158]. However, other investigators, using the same technique, failed to determine any meaningful effects of exercise training on forearm vascular conductance responses to such vasodilators as acetylcholine or sodium nitroprusside [159]. It is known that dynamic exercise leads to shedding of the cell adhesion molecule ICAM-1, but not E-selectin, via adrenergic mechanisms [160].…”
Section: Endothelial Markersmentioning
confidence: 99%